MOUNTAIN HIKERS’ ANXIETY DYNAMICS AND RISK PERCEPTION AS DETERMINANTS OF SUSTAINABILITY AWARENESS IN WEST JAVA’S MOUNTAINOUS AREAS - Fakhri Bhakti Noor; Nurul Rochmah Pramadika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Mountain hiking combines psychological challenges, perceived hazards, and environmental responsibilities that may influence hikers’ sustainability awareness. This study examined the effects of hikers’ anxiety and risk perception on sustainability awareness in mountain tourism areas of West Java, Indonesia. A quantitative explanatory design with a cross-sectional survey was employed. Data were collected from 250 hikers selected through purposive sampling at Mount Gede Pangrango, Mount Papandayan, Mount Ciremai, Mount Puntang, and Mount Burangrang. The research instrument consisted of 21 items measured using a five-point Likert scale. Data were analyzed using descriptive statistics and multiple linear regression. The results showed that hikers’ anxiety had a positive and significant effect on sustainability awareness (β = 0.204, t = 3.231, p = 0.001). Risk perception also had a positive and stronger significant effect on sustainability awareness (β = 0.631, t = 9.983, p < 0.001). Simultaneously, both variables significantly influenced sustainability awareness (F = 78.436, p < 0.001) and explained 38.8% of its variance. These findings demonstrate that emotional vigilance and cognitive risk assessment contribute to environmentally responsible awareness. Mountain destination managers should integrate safety communication,